Dyslipidaemia, diet and drugs - Dalby, Anthony J. (SA Heart Journal, 2017)
When considering dyslipidaemia, the cardiologist’s predominant concern is the relationship between serum low density lipoprotein cholesterol (LDLc) and the development of atherosclerotic cardiovascular disease (ASCVD). However, ASCVD is a multifactorial condition with its roots in our physical environment, the lifestyle we choose, our exposure to tobacco smoke, the diet to which we have become accustomed from a young age, the presence of specific morbidities: hypertension, diabetes, adiposity and elevated cholesterol levels, male sex and individual genetic propensities. Frequently these risk factors are found clustering in susceptible individuals. They ultimately find their expression as ASCVD and its complications as we age. Accepting the complexity of its origins, it is unsurprising that a multifaceted approach to the prevention of ASCVD, or its containment once it has emerged, is mandatory.